Pencerminan Nilai Persatuan Dan Tanggung Jawab Pada Pekerja(Studi Kasus pada Penggilingan Padi di UD. Fresto Gabah Desa Gerdu Kecamatan Pilangsari kabupaten Sragen) - Praditya, Rizki Dhimas; , Dra.Hj. Sri Arfiah, SH.M.Pd (2016)
This study aimed to describe the values of unity and responsibility arising from the working lives of workers in the rice milling UD. Grain Fresto Village Gerdu Pilangsari District of Sragen. The results are expected to contribute knowledge and information to the public about the values of unity and responsibility is important in social life. This study is a qualitative research conducted in the field (field research). This study uses qualitative research. This research was conducted at Rice mill UD. Grain Fresto Village Gerdu Pilangsari District of Sragen. Sources or informants in this study is the owner of the rice mill, rice mill workers at UD. Grain Fresto Village Gerdu Pilangsari District of Sragen. The data analysis using an interactive model. Reflecting the research results of unity and responsibility at the rice mill workers at UD. Grain Fresto showed that workers mutual preserve the values of unity and responsibility in the implementation of ekerjaaanya everyday, in the workers showed that the values of unity that emerged from the working lives of workers Rice mill at UD. Grain Fresto Village Gerdu Pilangsari District of Sragen is a sense of pride, happiness, cooperation, teamwork and helping each other. The values of the responsibility arising from the working lives of workers Rice mill at UD. Grain Fresto Village Gerdu Pilangsari District of Sragen is working happily, obey the rules, consistent with the words and admit mistakes. Maintaining the value of unity and responsibility in the life of the rice mill workers at UD. Fresto Grain is an attitude and behavior that are important in life because of the lack of unity and responsibility of a person would be careful in performing the act of doing so that the act of doing will be positive both for themselves and for others.